Needs Assessment on Inserting Oral Health Topics in General Medicine Educational Curriculum - Neda Babaee; Iman Jahanian; Ali Bijani; Jamil Samadi (Babol University of Medical Sciences, 2013)
ABSTRACT BACKGROUND AND OBJECTIVE: Integration of oral health promotion into general health care has been highly recommended by the World Health Organization. GPs can play an active role in the promotion of oral health care. Our aim was needs assessment for presentation of oral health topics in general medical students, training curriculum and to determine interventional method to improve their oral health knowledge by opinion poll among medical faculty authorities and members. METHODS: In this descriptive-analytic study conducted cross-sectionally, oral health knowledge and attitude of medical students of Babol University of Medical Sciences, who educated in third to sixth years of their course, were assessed by census. To comparison, 50 dental students in this university who educated in third to sixth years of their course and 50 engineering students who educated in third and fourth years of their course from Babol Noshirvani University of Technology were included by simple sampling. The means of data collection was a questionnaire. After analyzing the data, a survey on medical faculty authorities and members was conducted regarding to the necessity and how to plan the method of intervention for medical students in relation to oral health. FINDINGS: 319 students responded to the questionnaires. The mean age was 21.94±1.28, with an age range of 19-25 years. Mean and standard deviation scores were 8.02±3.41, 15.35±2.47 and 5.73±2.68 for medical, dental and engineering students, respectively. 61.7% of medical students have tendency to provide oral health topics in their academic courses. Medical faculty members of Babol University of Medical Sciences agreed with providing this topics as a part of public health course. CONCLUSION: Medical students' lack of knowledge about oral health and the positive attitudes of medical faculty authorities and members toward this subject, revealed a great need for inclusion of this topic in medical students, curriculum.